Perspectives on how to build bridges between regulation, health technology assessment and clinical guideline development: a qualitative focus group study with European experts - Marie Louise De Bruin; Aukje Mantel-Teeuwisse; Hubert G M Leufkens; Rick A Vreman; Junfeng Wang; Wim Goettsch; Milou A Hogervorst; Mathias Møllebæk; Ting-An Lu (BMJ Open, 2023)
Objective Improving synergy among regulation, health technology assessment (HTA) and clinical guideline development is relevant as these independent processes are building on shared evidence-based grounds. The two objectives were first to assess how convergence of evidentiary needs among stakeholders may be achieved, and second, to determine to what extent convergence can be achieved.Design Qualitative study using eight online dual-moderator focus groups.Setting Discussions had a European focus and were contextualised in four case studies on head and neck cancer, diabetes mellitus, multiple sclerosis and myelodysplastic syndromes.Participants Forty-two experienced (over 10 years) European regulators, HTA representatives and clinicians participated in the discussion.Interventions Participants received information on the case study and research topic in advance. An introductory background presentation and interview guide for the moderators were used to steer the discussion.Results Convergence may be achieved through improved communication institutionalised in multistakeholder early dialogues, shared definitions and shared methods. Required data sets should be inclusive rather than aligned. Deliberation and decision-making should remain independent. Alignment could be sought for pragmatic clinical trial designs and patient registries. Smaller and lower-income countries should be included in these efforts.Conclusion Actors in the field expressed that improving synergy among stakeholders always involves trade-offs. A balance needs to be found between the convergence of processes and the institutional remits or geographical independence. A similar tension exists between the involvement of more actors, for example, patients or additional countries, and the level of collaboration that may be achieved. Communication is key to establishing this balance.